Solar Cells
By using porous TiZnO3 as an electron transport material in tin-based perovskite solar cells, the voltage loss problem caused by energy level dissolution in the prior art is solved, and high flat band potential and high photoelectric conversion efficiency are achieved.
Patent Information
- Application Number
- CN201980081695.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-01-08
- Filing Date
- 2019-08-01
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2039-08-01
AI Technical Summary
The existing tin perovskite solar cells cannot output a voltage as high as expected due to their excellent physical properties. This is mainly due to the unconsolidation of energy levels between the electron transport material and the photoelectric conversion material, resulting in an increase in the probability of recombination of carriers near the interface, resulting in voltage loss.
The porous TiZnO3 is used as the electron transport material, and the electron transport layer is formed by spin coating to ensure that the energy level difference between the photoelectric conversion layer and the electron transport layer is small and the flat band potential is increased.
By using porous TiZnO3, the flat band potential of the solar cell is effectively improved, the photoelectric conversion efficiency is enhanced, and the high output voltage is achieved.
Smart Images

Figure CN113169279B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to solar cells. Background Art
[0002] In recent years, perovskite solar cells have been studied and developed. In perovskite solar cells, a perovskite compound represented by a chemical formula ABX3 (wherein A is a monovalent cation, B is a divalent cation, and X is a halogen anion) is used as a photoelectric conversion material.
[0003] Non-patent document 1 discloses a perovskite solar cell using a perovskite solar cell having a chemical formula of CH3NH3PbI 3-x Cl x (hereinafter referred to as "MAPbI 3-x Cl x The perovskite compound represented by ) is used as a photoelectric conversion material for perovskite solar cells.
[0004] In the perovskite solar cell disclosed in Non-Patent Document 1, Pb cations, TiO2-ZnO ternary oxide and 2,2′,7,7′-tetrakis(N,N-di-p-methoxyphenylamine)9,9′-spirobifluorene (hereinafter referred to as “Spiro-OMeTAD”) are used as divalent cations, electron transport materials and hole transport materials, respectively.
[0005] Non-patent document 2 discloses a lead-free perovskite solar cell. In the lead-free perovskite solar cell disclosed in Non-patent document 2, a perovskite compound represented by the chemical formula CsSnI3, TiO2 and Spiro-OMETAD are used as a photoelectric conversion material, an electron transport material and a hole transport material, respectively.
[0006] Prior art literature
[0007] Non-patent literature
[0008] Non-patent literature 1: Xiong Yin et al., "Ternary Oxides in the TiO2-ZnO System asEfficient Electron-Transport Layers for Perovskite Solar Cells with Efficiency over 15%", Applied Materials and Interfaces, 2016, 8, 29580-29587
[0009] Non-patent literature 2: Mulmudi Hemant Kumar et al., "Lead-free halide perovskite solarcells with high photocurrents realized through vacancy modulation", AdvancedMaterials, 2014, Volume 26, Issue 41, 7122-7127
[0010] Non-patent document 3: Antonio Guerrero et al., "Interfacial Degradation of PlanarLead Halide Perovskite Solar Cells", American Chemical Society Nano, 2016, Vol.10, Issue 1, pp218-224. Summary of the invention
[0011] Problems to be solved by the invention
[0012] The object of the present application is to provide a tin-based perovskite solar cell having a high flat band potential.
[0013] Means for solving problems
[0014] The solar cell of the present application has:
[0015] a first electrode;
[0016] a second electrode;
[0017] A photoelectric conversion layer disposed between the first electrode and the second electrode; and
[0018] an electron transport layer disposed between the first electrode and the photoelectric conversion layer,
[0019] At least one electrode selected from the first electrode and the second electrode is light-transmissive.
[0020] The photoelectric conversion layer contains a perovskite compound formed of a monovalent cation, a Sn cation, and a halogen anion.
[0021] The electron transport layer contains porous TiZnO3.
[0022] Effects of the Invention
[0023] The present application provides a tin-based perovskite solar cell with a high flat band potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 A cross-sectional view showing a solar cell according to an embodiment.
[0025] Figure 2 A cross-sectional view showing a modified example of the solar cell according to the embodiment. DETAILED DESCRIPTION
[0026] <Definition of terms>
[0027] The term "perovskite compound" used in this specification refers to a perovskite crystal structure represented by the chemical formula ABX3 (wherein A is a monovalent cation, B is a divalent cation, and X is a halogen anion) and a structure having a crystal similar thereto.
[0028] The term "tin-based perovskite compound" used in this specification refers to a perovskite compound containing tin.
[0029] The term "tin-based perovskite solar cell" used in this specification refers to a solar cell including a tin-based perovskite compound as a photoelectric conversion material.
[0030] The term "lead-based perovskite compound" used in this specification refers to a perovskite compound containing lead.
[0031] The term "lead-based perovskite solar cell" used in this specification refers to a solar cell including a lead-based perovskite compound as a photoelectric conversion material.
[0032] <Implementation Methods of the Application>
[0033] Hereinafter, embodiments of the present application will be described in detail with reference to the accompanying drawings.
[0034] like Figure 1 As shown in , the solar cell 100 of the present embodiment includes: a first electrode 2 ; a second electrode 6 ; a photoelectric conversion layer 4 provided between the first electrode 2 and the second electrode 6 ; and an electron transport layer 3 provided between the first electrode 2 and the photoelectric conversion layer 4 .
[0035] The first electrode 2 faces the second electrode 6 in such a manner that the electron transport layer 3 and the photoelectric conversion layer 4 are located between the first electrode 2 and the second electrode 6. At least one electrode selected from the first electrode 2 and the second electrode 6 has light transparency. In this specification, the term "the electrode has light transparency" means that among the light having a wavelength of 200 to 2000 nanometers, at any wavelength, 10% or more of the light is transmitted through the electrode.
[0036] (Photoelectric conversion layer 4)
[0037] The photoelectric conversion layer 4 contains a perovskite compound composed of monovalent cations, Sn cations, and halogen anions as a photoelectric conversion material. The photoelectric conversion material is a light absorbing material.
[0038] In the present embodiment, the perovskite compound may be a compound represented by a composition formula ABX3 (wherein A is a monovalent cation, B is a divalent cation including a Sn cation, and X is a halogen anion).
[0039] According to the expression consistently used for perovskite compounds, in this specification, A, B and X are also referred to as A site, B site and X site, respectively.
[0040] In this embodiment, the perovskite compound may have a perovskite crystal structure represented by a composition formula ABX3 (wherein A is a monovalent cation, B is a Sn cation, and X is a halogen anion). As an example, a monovalent cation is located at the A site, Sn is located at the B site, and X is located at the A site. 2+ is located at the B site, and the halogen anion is located at the X site.
[0041] The A site, B site and X site can also be occupied by multiple ions.
[0042] The B site contains Sn cations, i.e., Sn 2+ .
[0043] (A site)
[0044] The monovalent cation located at the A site is not limited. Examples of the monovalent cation A are organic cations or alkali metal cations. Examples of organic cations are methylammonium cations (i.e., CH3NH3 + ), carbamidinium cation (i.e. NH2CHNH2 + ), phenylethylammonium cation (i.e. C6H5C2H4NH3 + ) or guanidinium cation (i.e. CH6N3 + An example of an alkali metal cation is a cesium cation (i.e., Cs + ).
[0045] For high photoelectric conversion efficiency, the A site may contain at least one selected from the group consisting of a formamidinium cation and a methylammonium cation.
[0046] The phrase “the A site mainly contains at least one selected from the group consisting of formamidinium cations and methylammonium cations” means that the molar ratio of the total number of moles of formamidinium cations and methylammonium cations to the total number of moles of monovalent cations exceeds 50%.
[0047] The A site may be substantially composed of at least one selected from the group consisting of a formamidinium cation and a methylammonium cation.
[0048] The A site may mainly contain formamidinium cations. The phrase "the A site mainly contains formamidinium cations" means that the molar amount of formamidinium cations is the highest relative to the total molar amount of monovalent cations. The A site may be substantially composed of formamidinium cations only.
[0049] (X site)
[0050] An example of the halogen anion located at the X site is an iodide ion. The halogen anion located at the X site may also be composed of two or more halogen ions. For high photoelectric conversion efficiency, the halogen anion located at the X site preferably includes an iodide ion, for example.
[0051] The X site may also mainly contain iodide ions. "The halogen anions mainly contain iodide ions" means that the ratio of the molar amount of iodide ions to the total molar amount of halogen anions is the highest. The X site may also be substantially composed of iodide ions only.
[0052] The photoelectric conversion layer 4 may also contain materials other than the photoelectric conversion material. For example, the photoelectric conversion layer 4 may further contain a quenching substance for reducing the defect density of the perovskite compound. The quenching substance is a fluorine compound such as tin fluoride. The molar ratio of the quenching substance to the photoelectric conversion material may also be 5% to 20%.
[0053] (Photoelectric conversion layer 4)
[0054] The photoelectric conversion layer 4 may mainly contain a perovskite compound composed of monovalent cations, Sn cations, and halogen anions.
[0055] The phrase “the photoelectric conversion layer 4 mainly contains a perovskite compound formed of monovalent cations, Sn cations and halogen anions” means that the photoelectric conversion layer 4 contains 70 mass % or more (preferably 80 mass % or more) of a perovskite compound formed of monovalent cations, Sn cations and halogen anions.
[0056] Photoelectric conversion layer 4 may contain impurities. Photoelectric conversion layer 4 may further contain a compound other than the above-mentioned perovskite compound.
[0057] The photoelectric conversion layer 4 may have a thickness of 100 nanometers to 10 micrometers, preferably 100 nanometers to 1000 nanometers. The thickness of the photoelectric conversion layer 4 depends on the magnitude of its light absorption.
[0058] (Electron Transport Layer 3)
[0059] The electron transport layer 3 contains porous TiZnO3 as an electron transport material. The difference between the energy level at the lower end of the conduction band of the tin-based perovskite compound and the energy level at the lower end of the conduction band of TiZnO3 is small. As an example, the absolute value of the difference can be less than 0.2 eV. Due to this small difference, porous TiZnO3 is excellent as an electron transport material.
[0060] Since the electron transport layer 3 includes porous TiZnO 3 , the flat band potential of the solar cell in this embodiment can be improved.
[0061] The energy level at the lower end of the conduction band of the porous TiZnO 3 included in the electron transport layer 3 may be -4.0 eV to -3.0 eV based on the vacuum level.
[0062] The electron transport layer 3 may mainly contain porous TiZnO3 as the electron transport material. The term "the electron transport layer 3 mainly contains porous TiZnO3 as the electron transport material" means that the molar ratio of porous TiZnO3 contained in the electron transport layer 3 to the whole electron transport material is 50% or more (preferably 60% or more).
[0063] The electron transport material contained in the electron transport layer 3 may also be substantially composed of porous TiZnO3. "The electron transport material is substantially composed of porous TiZnO3" means that the ratio of porous TiZnO3 contained in the electron transport layer 3 to the whole electron transport material is 90 mol% or more (preferably 95 mol% or more).
[0064] The electron transport layer 3 may contain an electron transport material other than porous TiZnO 3. Hereinafter, for the sake of distinction, porous TiZnO 3 is sometimes referred to as a first electron transport material, and an electron transport material other than porous TiZnO 3 is sometimes referred to as a second electron transport material. The second electron transport material will be described below.
[0065] The term "porous" used in this specification refers to a substance having pores inside. That is, porous TiZnO3 refers to TiZnO3 having pores inside. As an example, in porous TiZnO3, TiZnO3 does not exist in the pores. Porous TiZnO3 may also have a plurality of pores. The sizes of the pores may be the same or different from each other.
[0066] The term "dense" used in this specification refers to a state in which a substance is gathered at a high density. Specifically, the term "dense" refers to a state in which the porosity is less than 10%. The porosity of a substance is calculated from the pore volume of the substance measured by a gas adsorption method and the density of the substance.
[0067] The electron transport layer 3 may also be in contact with the photoelectric conversion layer 4. Alternatively, the electron transport layer 3 may not be in contact with the photoelectric conversion layer 4. In the case where the electron transport layer 3 is in contact with the photoelectric conversion layer 4, porous TiZnO3 may also be provided on the surface of the electron transport layer 3 in contact with the photoelectric conversion layer 4. That is, porous TiZnO3 may also be in contact with the photoelectric conversion layer 4. In the case where porous TiZnO3 is in contact with the photoelectric conversion layer 4, the flat band potential of the solar cell is further improved.
[0068] The electron transport layer 3 may be composed of a plurality of layers formed of different electron transport materials. When the electron transport layer 3 is composed of a plurality of layers, the layer in contact with the photoelectric conversion layer 4 may contain porous TiZnO 3 .
[0069] As an example, the electron transport layer 3 has a multilayer structure of a layer composed of dense TiZnO 3 and a layer composed of porous TiZnO 3 , and the layer composed of porous TiZnO 3 is in contact with the photoelectric conversion layer 4 .
[0070] The porous TiZnO3 contained in the electron transport layer 3 is a titanium-zinc composite oxide having a Ti:Zn:O molar ratio of approximately 1:1:3. The porous TiZnO3 in the present embodiment may also include a titanium-zinc composite oxide having a composition ratio slightly deviated from Ti:Zn:O=1:1:3 (for example, within the range of ±0.5) within a range that can obtain the same effect as the porous TiZnO3.
[0071] The composition ratio of porous TiZnO3 can be determined by the following methods: X-ray photoelectron spectroscopy (hereinafter referred to as "XPS method"), energy dispersive X-ray analysis (hereinafter referred to as "EDX method"), inductively coupled plasma emission spectrometry (hereinafter referred to as "ICP-OES method"), or Rutherford backscattering analysis (hereinafter referred to as "RBS method").
[0072] The porous TiZnO3 contained in the electron transport layer 3 may have a porosity of 20% to 70%. From the viewpoint of effectively improving the flat band potential of the solar cell, the porosity is preferably 20% or more. On the other hand, from the viewpoint of maintaining the structure of the electron transport layer 3, the porosity is preferably 70% or less. As demonstrated in the examples described later, the preferred porosity is 48% to 60%. In this way, by using porous TiZnO3 having a porosity of 20% to 70%, both a high flat band potential and a low carrier density (i.e., a low doping density) can be achieved. In Sn perovskite compounds, Sn 2+ Easily oxidized to Sn 4+As a result, Sn defects are easily generated. Therefore, in Sn perovskite compounds, there is a tendency for the carrier density to be higher than that of Pb perovskite compounds. If the carrier density (i.e., defect density) of the Sn perovskite compound is high, it becomes easy to cause recombination of carriers. As a result, the characteristics of devices having Sn perovskite compounds are reduced.
[0073] As described above, the porosity is preferably 48% to 60%. From the viewpoint of being able to more effectively increase the flat band potential of the solar cell, the porosity is more preferably 48% or more. On the other hand, from the viewpoint of maintaining the structure of the electron transport layer 3, the porosity is more preferably 60% or less. In this way, by using porous TiZnO3 having a porosity of 48% to 60%, both a higher flat band potential and a lower carrier density can be achieved compared to dense TiZnO3.
[0074] Next, the second electron transport material (that is, an electron transport material other than porous TiZnO 3 ) will be described.
[0075] The electron transport layer 3 may contain not only porous TiZnO 3 but also dense TiZnO 3. That is, the second electron transport material may be dense TiZnO 3.
[0076] The second electron transport material may be a material known as an electron transport material for solar cells.
[0077] The second electron transport material may also be a semiconductor having a band gap of 3.0 eV or more. When the electron transport layer 3 contains a semiconductor having a band gap of 3.0 eV or more, visible light and infrared light reach the photoelectric conversion layer 4 via the substrate 1, the first electrode 2, and the electron transport layer 3. Examples of semiconductors having a band gap of 3.0 eV or more are organic or inorganic n-type semiconductors.
[0078] Examples of organic n-type semiconductors are imide compounds, quinone compounds, fullerenes, or fullerene derivatives.
[0079] Examples of inorganic n-type semiconductors are metal oxides, metal nitrides or perovskite oxides.
[0080] Examples of metal oxides are Cd, Zn, In, Pb, Mo, W, Sb, Bi, Cu, Hg, Ti, Ag, Mn, Fe, V, Sn, Zr, Sr, Ga, Si or Cr. TiO2 is preferred.
[0081] An example of a metal nitride is GaN.
[0082] Examples of perovskite oxides are SrTiO3 or CaTiO3.
[0083] From the viewpoint of sufficient electron transport properties of the electron transport layer 3 and low resistance of the electron transport layer 3 , the electron transport layer 3 may have a thickness of 1 nm to 500 nm in order to improve the photoelectric conversion efficiency of the solar cell.
[0084] like Figure 1 As shown in , the electron transport layer 3 may be composed of a dense layer 3a composed of a dense electron transport material (eg, TiZnO 3 ) and a porous layer 3b composed of porous TiZnO 3 .
[0085] The porous layer 3b facilitates the formation of the photoelectric conversion layer 4. The material of the photoelectric conversion layer 4 intrudes into the inside of the pores of the porous layer 3b. Due to the infiltration, the porous layer 3b becomes a foothold of the photoelectric conversion layer 4. Since the porous layer 3b is provided, it is not easy to cause the photoelectric conversion material to be repelled or aggregated on the surface of the dense layer 3a. Therefore, the porous layer 3b makes it easy to form the photoelectric conversion layer 4 in the form of a uniform film.
[0086] Light scattering occurs when passing through the porous layer 3b. The light scattering increases the optical path length of light passing through the photoelectric conversion layer 4. The increase in the optical path length increases the amount of electrons and holes generated in the photoelectric conversion layer 4.
[0087] The dense layer 3a is in contact with the first electrode 2. The dense layer 3a is a dense layer containing an electron transport material.
[0088] The porous layer 3b is composed of porous TiZnO 3. The porous layer 3b may further contain a substance other than porous TiZnO 3 as an additive.
[0089] The pores in the porous layer 3b may also be connected from the portion in contact with the dense layer 3a to the portion in contact with the photoelectric conversion layer 4. The pores contained in the porous layer 3b may also be filled with the material of the photoelectric conversion layer 4. Furthermore, the material of the photoelectric conversion layer 4 may also reach the surface of the dense layer 3a. Therefore, the electrons generated in the photoelectric conversion layer 4 may reach the dense layer 3a via the porous layer 3b, or directly reach the dense layer 3a without the porous layer 3b. The electrons reaching the dense layer 3a move to the first electrode 2.
[0090] Figure 1 A cross-sectional view of a solar cell according to an embodiment is shown. Figure 1 As shown in FIG. 1 , in the solar cell 100, a first electrode 2, an electron transport layer 3, a photoelectric conversion layer 4, a hole transport layer 5, and a second electrode 6 are sequentially stacked on a substrate 1. The solar cell 100 may not include the substrate 1. The solar cell 100 may not include the hole transport layer 5.
[0091] (Substrate 1)
[0092] The substrate 1 holds the first electrode 2, the photoelectric conversion layer 4, and the second electrode 6. The substrate 1 can be formed of a transparent material. An example of the substrate 1 is a glass substrate or a plastic substrate. An example of a plastic substrate is a plastic film. When the first electrode 2 has sufficient strength, the first electrode 2 holds the photoelectric conversion layer 4 and the second electrode 6, so the solar cell 100 may not have the substrate 1.
[0093] (First Electrode 2 and Second Electrode 6)
[0094] The first electrode 2 and the second electrode 6 are conductive. At least one electrode selected from the first electrode 2 and the second electrode 6 is light-transmissive. Light in the visible region to the near-infrared region can pass through the light-transmissive electrode. The light-transmissive electrode can be formed of a transparent and conductive material.
[0095] Examples of such materials are:
[0096] (i) titanium oxide doped with at least one selected from lithium, magnesium, niobium and fluorine,
[0097] (ii) gallium oxide doped with at least one selected from tin and silicon,
[0098] (iii) gallium nitride doped with at least one selected from silicon and oxygen,
[0099] (iv) indium-tin composite oxide,
[0100] (v) tin oxide doped with at least one selected from antimony and fluorine,
[0101] (vi) zinc oxide doped with at least one of boron, aluminum, gallium, and indium, or
[0102] (vii) Complexes thereof.
[0103] The light-transmitting electrode can be formed by setting a light-transmitting pattern using an opaque material. Examples of light-transmitting patterns are linear, wavy, lattice, or punched metal-like patterns in which a large number of fine through holes are regularly or irregularly arranged. If the light-transmitting electrode has these patterns, light can pass through the part where the electrode material is not present. Examples of opaque materials are platinum, gold, silver, copper, aluminum, rhodium, indium, titanium, iron, nickel, tin, zinc, or an alloy containing any of them. Conductive carbon materials can also be used as opaque materials.
[0104] Since the solar cell 100 includes the electron transport layer 3 between the photoelectric conversion layer 4 and the first electrode 2, the first electrode 2 may not have a barrier property against holes from the photoelectric conversion layer 4. Therefore, the material of the first electrode 2 may be a material that can make ohmic contact with the photoelectric conversion layer 4.
[0105] In the case where the solar cell 100 does not include the hole transport layer 5, the second electrode 6 is formed of, for example, a material having a barrier property against electrons from the photoelectric conversion layer 4. In this case, the second electrode 6 is not in ohmic contact with the photoelectric conversion layer 4. The barrier property against electrons from the photoelectric conversion layer 4 refers to the property of allowing only holes generated in the photoelectric conversion layer 4 to pass through, but not electrons. The Fermi energy of the material having a barrier property against electrons is lower than the energy level at the lower end of the conduction band of the photoelectric conversion layer 4. The Fermi energy of the material having a barrier property against electrons may also be lower than the Fermi energy level of the photoelectric conversion layer 4. Examples of materials having a barrier property against electrons are platinum, gold, or carbon materials such as graphene.
[0106] Regarding the solar cell 100, when the hole transport layer 5 is provided between the photoelectric conversion layer 4 and the second electrode 6, the second electrode 6 may not have a barrier property against electrons from the photoelectric conversion layer 4. In this case, the second electrode 6 may be in ohmic contact with the photoelectric conversion layer 4.
[0107] The material having a blocking property for holes from the photoelectric conversion layer 4 may not be light-transmitting. The material having a blocking property for electrons from the photoelectric conversion layer 4 may not be light-transmitting. Therefore, when the first electrode 2 or the second electrode 6 is formed using these materials, the first electrode 2 or the second electrode 6 has the above-mentioned pattern that allows light to pass through the first electrode 2 or the second electrode 6.
[0108] The light transmittance of each of the first electrode 2 and the second electrode 6 may be 50% or more, or 80% or more. The wavelength of light transmitted through the electrodes depends on the absorption wavelength of the photoelectric conversion layer 4. The thickness of each of the first electrode 2 and the second electrode 6 is, for example, in the range of 1 nm to 1000 nm.
[0109] (Hole Transport Layer 5)
[0110] The hole transport layer 5 is composed of an organic substance or an inorganic semiconductor. Representative examples of organic substances used as the hole transport layer 5 are 2,2′,7,7′-tetrakis-(N,N-di-p-methoxyphenylamine)9,9′-spirobifluorene (hereinafter referred to as “spiro-OMeTAD”), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (hereinafter referred to as “PTAA”), poly(3-hexylthiophene-2,5-diyl) (hereinafter referred to as “P3HT”), poly(3,4-ethylenedioxythiophene) (hereinafter referred to as “PEDOT”), or copper phthalocyanine (hereinafter referred to as “CuPC”).
[0111] Examples of inorganic semiconductors are Cu2O, CuGaO2, CuSCN, CuI, NiO x 、MoO x , V2O5 or carbon materials such as graphene oxide.
[0112] The hole transport layer 5 may include a plurality of layers formed of materials different from each other.
[0113] The thickness of the hole transport layer 5 may be 1 nm to 1000 nm, 10 nm to 500 nm, or 10 nm to 50 nm. If the thickness of the hole transport layer 5 is 1 nm to 1000 nm, sufficient hole transport properties can be achieved. Furthermore, if the thickness of the hole transport layer 5 is 1 nm to 1000 nm, the resistance of the hole transport layer 5 is low, so light is efficiently converted into electricity.
[0114] The hole transport layer 5 may contain a supporting electrolyte and a solvent. The supporting electrolyte and the solvent stabilize the holes in the hole transport layer 5 .
[0115] Examples of supporting electrolytes are ammonium salts or alkali metal salts. Examples of ammonium salts are tetrabutylammonium perchlorate, tetraethylammonium hexafluorophosphate, imidazolium salts or pyridinium salts. Examples of alkali metal salts are lithium bis(trifluoromethanesulfonyl)imide (hereinafter referred to as "LiTFSI"), LiPF6, LiBF4, lithium perchlorate or potassium tetrafluoroborate.
[0116] The solvent contained in the hole transport layer 5 may also have high ion conductivity. The solvent may be an aqueous solvent or an organic solvent. From the viewpoint of stabilization of the solute, an organic solvent is preferred. Examples of organic solvents are heterocyclic compounds such as tert-butylpyridine, pyridine, or N-methylpyrrolidone.
[0117] The solvent contained in the hole transport layer 5 may be an ionic liquid. The ionic liquid may be used alone or in a mixture with other solvents. The ionic liquid is preferred from the viewpoint of low volatility and high flame retardancy.
[0118] Examples of the ionic liquid include imidazolium compounds such as 1-ethyl-3-methylimidazolium tetracyanoborate, pyridine compounds, alicyclic amine compounds, aliphatic amine compounds, or azoinium amine compounds.
[0119] Figure 2 A cross-sectional view showing a modified example of the solar cell according to the embodiment.
[0120] Figure 2 The solar cell 200 shown in FIG. 1 is similar to the solar cell 200 shown in FIG. 1 except that the electron transport layer 3 is composed of only the porous layer 3 b. Figure 1 The solar cell 200 does not include the dense layer 3 a , but the basic functions and effects of the solar cell 200 are the same as those of the solar cell 100 .
[0121] Next, the basic effects of the solar cell 100 will be described. When the solar cell 100 is irradiated with light, the photoelectric conversion layer 4 absorbs the light, and excited electrons and holes are generated inside the photoelectric conversion layer 4. The excited electrons move to the electron transport layer 3. On the other hand, the holes generated in the photoelectric conversion layer 4 move to the hole transport layer 5. The electron transport layer 3 is connected to the first electrode 2, and the hole transport layer 5 is connected to the second electrode 6, so that current is extracted from the first electrode 2 functioning as a negative electrode and the second electrode 6 functioning as a positive electrode.
[0122] (Method of Manufacturing Solar Cell 100)
[0123] The solar cell 100 can be produced, for example, by the following method.
[0124] First, the first electrode 2 is formed on the surface of the substrate 1 by chemical vapor deposition (hereinafter referred to as “CVD”) or sputtering.
[0125] On the first electrode 2, a dense layer 3a is formed by a coating method such as a spin coating method or a sputtering method. The following is a method for forming a dense layer 3a composed of dense TiZnO3. In the spin coating method, a solution obtained by dissolving a Ti raw material and a Zn raw material is prepared. An example of the Ti raw material is tetraisopropyl orthotitanate or TiCl4. An example of the Zn raw material is ZnCl2 or zinc acetate. An example of a solvent for the solution is isopropyl alcohol or ethanol.
[0126] The solution is applied onto the first electrode 2 by spin coating to form a coating film. The coating film is fired at a temperature of 30 degrees Celsius to 700 degrees Celsius in air.
[0127] On top of the dense layer 3a, a porous layer 3b is formed by a coating method such as a spin coating method. As described above, the porous layer 3b is composed of porous TiZnO3. In the spin coating method, a solution obtained by dissolving a Ti raw material and a Zn raw material is prepared. Examples of the Ti raw material are tetrabutyl orthotitanate or TiCl4. Examples of the Zn raw material are ZnCl2, zinc nitrate hexahydrate, or zinc acetate. Examples of the solution solvent are ethanol, benzyl alcohol, or 1,3-propanediol.
[0128] The solution is heated to obtain a TiZnO3 dispersion. A porogen is added to the obtained TiZnO3 dispersion to prepare a porous TiZnO3 raw material solution. An example of the porogen is ethyl cellulose.
[0129] The porous TiZnO3 raw material solution is coated on top of the dense layer 3a by a spin coating method to form a coating film. The coating film is fired at a temperature of 100 °C to 700 °C. By operating in this way, the porous layer 3b is formed.
[0130] A photoelectric conversion layer 4 is formed on top of the electron transport layer 3 (i.e., on top of the porous layer 3b). The photoelectric conversion layer 4 can be formed, for example, as follows. Hereinafter, as an example, a method for forming a photoelectric conversion layer 4 containing a perovskite compound represented by (HC(NH2)2) 1-y (C6H5CH2CH2NH3) y SnI3 (where 0 < y < 1, hereinafter referred to as "FA 1-y-z PEA y SnI3") will be described.
[0131] First, SnI2, HC(NH2)2I (hereinafter referred to as "FAI"), and C6H5CH2CH2NH3I (hereinafter referred to as "PEAI") are added to an organic solvent to obtain a mixed solution. Examples of the organic solvent are a mixture of dimethyl sulfoxide (hereinafter referred to as "DMSO") and N,N-dimethylformamide (hereinafter referred to as "DMF") (volume ratio = 1:1).
[0132] The molar concentration of SnI2 can also be 0.8 mol / L to 2.0 mol / L, or can also be 0.8 mol / L to 1.5 mol / L.
[0133] The molar concentration of FAI can also be 0.8 mol / L to 2.0 mol / L, or can also be 0.8 mol / L to 1.5 mol / L.
[0134] The molar concentration of PEAI can also be 0.1 mol / L to 0.6 mol / L, or can also be 0.3 mol / L to 0.5 mol / L.
[0135] Next, the mixed solution is heated to a temperature of 40 degrees Celsius to 180 degrees Celsius. In this way, a mixed solution in which SnI2, FAI and PEAI are dissolved is obtained. Next, the mixed solution is left at room temperature.
[0136] Next, the mixed solution is applied to the electron transport layer 3 (i.e., on the porous layer 3b) by spin coating to form a coating film. Next, the coating film is heated at a temperature of 40°C to 100°C for 15 minutes to 1 hour. Thus, the photoelectric conversion layer 4 is formed. When the mixed solution is applied by spin coating, a poor solvent may be added dropwise during the spin coating. Examples of the poor solvent are toluene, chlorobenzene, or diethyl ether.
[0137] The mixed solution may also contain a quenching substance such as tin fluoride. The concentration of the quenching substance may also be 0.05 mol / L to 0.4 mol / L. The quenching substance can suppress the generation of defects in the photoelectric conversion layer 4. The cause of the generation of defects in the photoelectric conversion layer 4 is, for example, due to Sn 4+ The increase in the amount of Sn causes the increase in Sn vacancies.
[0138] A hole transport layer 5 is formed on the photoelectric conversion layer 4. Examples of a method for forming the hole transport layer 5 include a coating method or a printing method. Examples of coating methods include a doctor blade method, a rod coating method, a spray method, a dip coating method, or a spin coating method. An example of a printing method is a screen printing method. It is also possible to mix a plurality of materials to obtain the hole transport layer 5, and then pressurize or sinter the hole transport layer 5. When the material of the hole transport layer 5 is an organic low molecular weight body or an inorganic semiconductor, the hole transport layer 5 can also be produced by a vacuum evaporation method.
[0139] Finally, the second electrode 6 is formed on the hole transport layer 5. In this way, the solar cell 100 is obtained. The second electrode 6 can be formed by a CVD method or a sputtering method.
[0140] <Understanding that forms the basis of this application>
[0141] The knowledge that forms the basis of the present application is as follows.
[0142] Tin-based perovskite compounds have excellent physical properties as photoelectric conversion materials. Therefore, tin-based perovskite solar cells can be expected to output high voltages. However, in reality, conventional tin-based perovskite solar cells cannot output the high voltages expected from their excellent physical properties.
[0143] Generally speaking, it is known that one of the factors that cause the voltage of a solar cell to drop is that the energy level at the lower end of the conduction band of the electron transport material and the energy level at the lower end of the conduction band of the photoelectric conversion material are not integrated. More specifically, when this integration is not achieved, the probability of the existence of electrons near the interface between the electron transport layer 3 and the photoelectric conversion layer 4 increases. As a result, the probability of recombination of carriers at the interface increases, resulting in a loss of voltage. The value of the "energy level at the lower end of the conduction band" in this specification is a value based on the vacuum energy level.
[0144] The energy level at the lower end of the conduction band of tin-based perovskite compounds can be approximately -3.4 eV. The representative electron transport material used in the past in tin-based perovskite solar cells is TiO2. The energy level at the lower end of the conduction band of TiO2 is -4.0 eV. The difference between them is as large as 0.6 eV. This large value is the reason why conformity is not achieved.
[0145] As such, in conventional tin-based perovskite solar cells, there is no compatibility between the energy level at the lower end of the conduction band of the electron transport material and the energy level at the lower end of the conduction band of the photoelectric conversion material. The inventors of the present invention have discovered that in order to increase the output voltage of a tin-based perovskite solar cell, it is considered necessary to use an electron transport material having an energy level at the lower end of the conduction band that is shallower than the energy level at the lower end of the conduction band of TiO2.
[0146] The inventors of the present invention focused on TiZnO 3 as an electron transport material. The reason why the inventors of the present invention focused on TiZnO 3 is that the difference between the energy level at the lower end of the conduction band of TiZnO 3 and the energy level at the lower end of the conduction band of the tin-based perovskite compound is small.
[0147] The energy level at the lower end of the conduction band of TiZnO3 is -3.2eV. That is, TiZnO3 has a shallower energy level at the lower end of the conduction band than TiO2, which is a general electron transport material of a conventional tin-based perovskite solar cell. As described above, the energy level at the lower end of the conduction band of a tin-based perovskite solar cell is -3.4eV. Therefore, the difference between them is a small value of 0.2eV. Due to this small difference in energy levels, TiZnO3 is suitable as an electron transport material contained in a tin-based perovskite solar cell.
[0148] However, it is difficult to improve the flat band potential when TiZnO 3 is used as an electron transport material. The inventors of the present invention have newly found that the flat band potential can be effectively improved by using a porous body of TiZnO 3 as an electron transport material.
[0149] Based on these findings, the inventors of the present invention provide a solar cell containing a tin-based perovskite compound and having a high flat band potential.
[0150] (Example)
[0151] Hereinafter, the present application will be described in more detail with reference to the following examples. As described below, in Examples 1 to 4 and Comparative Examples 1 to 5, a solar cell having an electron transport layer 3 and a photoelectric conversion layer 4 containing a perovskite compound was prepared. Furthermore, the characteristics of each solar cell were evaluated. Each solar cell of Examples 1 to 4 and Comparative Examples 1 to 3 has Figure 1 The tin-based perovskite solar cell has the same structure as the perovskite solar cell 100 shown in FIG. The solar cells of Comparative Examples 4 to 5 also have Figure 1 It should be noted that the solar cells of Comparative Examples 4 and 5 are not tin-based lead perovskite solar cells but lead-based perovskite solar cells.
[0152] (Example 1)
[0153] A glass substrate (manufactured by Nippon Sheet Glass Co., Ltd.) having a SnO2 layer doped with indium on its surface was prepared. The glass substrate and the SnO2 layer functioned as a substrate 1 and a first electrode 2, respectively. The glass substrate had a thickness of 1 mm.
[0154] Tetraisopropyl orthotitanate (manufactured by Sigma-Aldrich, hereinafter referred to as "TTIT") and zinc chloride (manufactured by FUJIFILM Wako Pure Chemical Corporation) were dissolved in isopropyl alcohol (manufactured by FUJIFILM Wako Pure Chemical Corporation, hereinafter referred to as "IPA") to prepare an IPA solution. The concentration of TTIT contained in the IPA solution was 15 mmol / L. The concentration of zinc chloride contained in the IPA solution was 6.5 mmol / L.
[0155] The IPA solution was applied onto the first electrode 2 by spin coating to obtain a coating film. The coating film was fired at 350 degrees Celsius in air for 1 hour to form a dense layer 3a.
[0156] The dense layer 3a has a thickness of 10 nanometers.
[0157] The molar ratio of Ti:Zn in the dense layer 3 a is 15:6.5.
[0158] Next, the porous layer 3 b is formed in the following manner.
[0159] First, zinc nitrate hexahydrate (1.356 g, manufactured by FUJIFILM Wako Pure Chemical Corporation) was dissolved in ethanol (3.185 mL, manufactured by FUJIFILM Wako Pure Chemical Corporation) to obtain an ethanol solution containing zinc nitrate hexahydrate at a concentration of 1.43 mol / L.
[0160] Tetrabutyl titanate (4.56 mmol) was added dropwise to the ethanol solution to obtain a mixed solution, and the mixed solution was stirred.
[0161] The molar ratio of Ti to Zn was 1.
[0162] Benzyl alcohol (9.61 mL, manufactured by Kanto Chemical Co., Ltd.) and 1,3-propylene glycol (0.113 mL, manufactured by Sigma-Aldrich) were added to the mixed solution. After the addition, the mixed solution was heated at 80°C for 8 hours to prepare a TiZnO3 dispersion.
[0163] Ethyl cellulose (0.178 g) was dissolved in ethanol (8.06 ml), and then terpineol (45 μl) was added to prepare an ethanol solution of ethyl cellulose. The ethyl cellulose contained in the ethanol solution had a concentration of 5.3% by mass.
[0164] The TiZnO 3 dispersion prepared as described above and the ethyl cellulose ethanol solution were mixed so as to have a TiZnO 3 : ethyl cellulose mass ratio of 1 : 0.27. In this manner, a porous TiZnO 3 raw material solution was prepared.
[0165] The porous TiZnO3 raw material solution is applied to the dense layer 3a by a spin coating method to form a coating film. The coating film is quasi-fired at 80 degrees Celsius for 10 minutes. Thereafter, the quasi-fired film is placed in an electric furnace and fired at 400 degrees Celsius for 4 hours to form a porous layer 3b formed of porous TiZnO3. The composition of the material constituting the porous layer 3b, TiZnO3, is expressed based on the molar ratio of Ti to Zn in the starting material.
[0166] In this manner, the electron transport layer 3 including the dense layer 3 a and the porous layer 3 b is formed.
[0167] Next, a solution containing SnI2 (manufactured by Sigma-Aldrich), SnF2 (manufactured by Sigma-Aldrich), FAI (manufactured by GreatCell Solar), and PEAI (manufactured by Great Cell Solar) was prepared. The concentrations of SnI2, SnF2, FAI, and PEAI contained in the solution were 1.5 mol / L, 0.15 mol / L, 1.5 mol / L, and 0.3 mol / L, respectively. The solvent of the solution was a mixture of DMSO (i.e., dimethyl sulfoxide) and DMF (i.e., N,N-dimethylformamide) (DMSO:DMF=1:1 (volume ratio)).
[0168] In the glove box, the solution (80 microliters) was applied to the electron transport layer 3 by spin coating to form a coating film. The coating film had a thickness of 450 nanometers. A portion of the solution also infiltrated the inside of the pores of the porous layer 3b. Therefore, the thickness of the coating film (i.e., 450 nanometers) included the thickness of the porous layer 3b. The thickness of the porous layer 3b was 224 nanometers.
[0169] The coating film was baked on a hot plate at 80 degrees Celsius for 30 minutes to form a photoelectric conversion layer 4. The photoelectric conversion layer 4 mainly contains a composition formula FA 0.83 PEA 0.17 Perovskite compound represented by SnI3. Composition formula FA 0.83 PEA 0.17 The energy level at the lower end of the conduction band of the perovskite compound represented by SnI3 is -3.4 eV based on the vacuum level.
[0170] In a glove box, a toluene solution (80 μL) containing PTAA (poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine, manufactured by Sigma-Aldrich) at a concentration of 10 mg / mL was applied on the photoelectric conversion layer 4 by spin coating to form the hole transport layer 5 .
[0171] Finally, a gold film having a thickness of 100 nanometers was deposited on the hole transport layer 5 to form the second electrode 6. In this manner, the solar cell of Example 1 was obtained.
[0172] [Example 2]
[0173] In Example 2, the solar cell of Example 2 is obtained by the same method as Example 1 except that a porous TiZnO3 raw material solution is prepared by mixing a TiZnO3 dispersion and an ethanol solution of ethyl cellulose in a TiZnO3:ethyl cellulose mass ratio of 1:1.2.
[0174] [Example 3]
[0175] In Example 3, the solar cell of Example 3 was obtained by the same method as Example 1 except that the TiZnO3 dispersion and the ethanol solution of ethyl cellulose were mixed in a manner having a TiZnO3:ethyl cellulose mass ratio of 1:7.2 to prepare a porous TiZnO3 raw material solution.
[0176] [Example 4]
[0177] In Example 4, a solar cell of Example 4 was obtained by the same method as in Example 1 except for the following two matters (i) and (ii).
[0178] (i) In the formation of the dense layer 3a, the concentrations of TTIT and zinc chloride contained in the IPA solution were 10.8 mmol / L and 10.8 mmol / L, respectively, so that the molar ratio of Ti:Zn contained in the starting material became equal to 1:1;
[0179] (ii) As in Example 3, a TiZnO 3 dispersion and an ethyl cellulose ethanol solution were mixed so as to have a TiZnO 3 :ethyl cellulose mass ratio of 1:7.2 to prepare a porous TiZnO 3 raw material solution.
[0180] [Comparative Example 1]
[0181] In Comparative Example 1, except that the porous layer 3 b was not formed, a solar cell of Comparative Example 1 was obtained by the same method as in Example 1. That is, the electron transport layer 3 of the solar cell of Comparative Example 1 did not contain porous TiZnO 3 .
[0182] [Comparative Example 2]
[0183] In Comparative Example 2, a solar cell of Comparative Example 2 was obtained by the same method as in Example 1 except for the following two matters (i) and (ii).
[0184] (i) The dense layer 3a is formed by forming titanium oxide represented by the chemical formula TiO2 on the first electrode 2 by a sputtering method.
[0185] (ii) The porous layer 3b is formed as follows.
[0186] First, titanium oxide powder (manufactured by Great Cell Solar) having an average primary particle size of 30 nanometers was dispersed in an ethyl cellulose ethanol solution to prepare a TiO2 paste.
[0187] Next, the TiO2 paste was applied onto the dense layer 3a to obtain a coating film, and the coating film was calcined at 100 degrees Celsius.
[0188] Finally, the calcined coating film was calcined in air at 500 degrees Celsius for 30 minutes to form a porous layer 3b.
[0189] [Comparative Example 3]
[0190] In Comparative Example 3, a solar cell of Comparative Example 3 was obtained by the same method as in Example 1 except for the following matter (i).
[0191] (i) In the formation of the porous layer 3b, the weight of zinc nitrate hexahydrate was 1.356 g. In Comparative Example 3, the molar ratio of Ti:Zn contained in the starting material was equal to 3:1, and the zinc nitrate hexahydrate contained in the ethanol solution was 0.48 mol / L.
[0192] [Comparative Example 4]
[0193] In Comparative Example 4, the photoelectric conversion layer 4 is not composed of the composition formula FA 0.83 PEA 0.17 SnI3 is a tin-based perovskite compound, but it is composed of FA 0.83 PEA 0.17 A solar cell of Comparative Example 4 was obtained by the same method as in Example 1 except that the lead-based perovskite compound represented by PbI 3 was used.
[0194] By FA 0.83 PEA 0.17 The lead-based perovskite compound represented by PbI3 is the same as that of Example 1 with the composition formula FA except that PbI2 (manufactured by Sigma-Aldrich, 1.5 mol / L) is used instead of SnI2 (1.5 mol / L) and SnF2 (0.15 mol / L). 0.83 PEA 0.17 The same is true for the case of a tin-based perovskite compound represented by SnI3.
[0195] Composition FA 0.83 PEA 0.17 The energy level at the lower end of the conduction band of the PbI3 perovskite compound is -4.0 eV based on the vacuum level.
[0196] [Comparative Example 5]
[0197] In Comparative Example 5, a solar cell of Comparative Example 5 was obtained by the same method as in Example 1 except for the following three matters (i) to (iii).
[0198] (i) As in the case of Comparative Example 2, the dense layer 3 a is formed by forming titanium oxide represented by the chemical formula TiO 2 on the first electrode 2 by sputtering.
[0199] (ii) As in the case of Comparative Example 2, the porous layer 3b is formed as follows. First, titanium oxide powder (manufactured by Great Cell Solar) having an average primary particle size of 30 nanometers is dispersed in an ethanol solution of ethyl cellulose to prepare a TiO2 paste. Next, the TiO2 paste is applied to the dense layer 3a to obtain a coating film. The coating film is quasi-fired at 100 degrees Celsius. Finally, the quasi-fired coating film is fired in air at 500 degrees Celsius for 30 minutes to form a porous layer 3b.
[0200] (iii) As in the case of Comparative Example 4, the photoelectric conversion layer 4 is not composed of the composition formula FA 0.83 PEA 0.17 SnI3 is a tin-based perovskite compound, but it is composed of FA 0.83 PEA 0.17 Lead-based perovskite compounds represented by PbI3.
[0201] [Calculation of the Energy Level at the Lower End of the Conduction Band of the Electron Transport Material Contained in the Porous Layer 3 b ]
[0202] In each of the examples and comparative examples, a sample was prepared which consisted of a substrate 1, a first electrode 2, and an electron transport layer 3. The sample did not include a photoelectric conversion layer 4, a hole transport layer 5, and a second electrode 6. That is, the surface of the electron transport layer 3 was exposed.
[0203] The energy level of the lower end of the conduction band of the electron transport material contained in the porous layer 3b of the electron transport layer 3 contained in the sample was measured by ultraviolet electron spectroscopy and transmittance measurement as follows. In Comparative Example 1, the energy level of the lower end of the conduction band of the electron transport material contained in the dense layer 3a was measured.
[0204] Each sample was subjected to ultraviolet electron spectrometry using an ultraviolet electron spectrometer (manufactured by ULVAC-PHI Co., Ltd., trade name: PHI5000Versa Probe) to obtain the energy level value of the upper end of the valence electron band of each electron transport material.
[0205] Each sample was subjected to transmittance measurement using a transmittance measuring apparatus (manufactured by Shimadzu Corporation, trade name: Slid Spec-3700)), and then the band gap value of each electron transport material was obtained from the transmittance measurement results.
[0206] Based on the energy level at the upper end of the valence band and the band gap value obtained in this manner, the energy level at the lower end of the conduction band of the electron transport material is calculated.
[0207] The energy level at the lower end of the conduction band of each material calculated in this manner is as follows.
[0208]
[0209] [Porosity of the porous layer 3b]
[0210] The porosity of the porous layer 3b of the embodiment and the comparative example is calculated from the pore volume of the porous layer 3b obtained by a gas adsorption measurement method using a gas adsorption device (manufactured by Micromeritics, trade name: ASAP) and the density of the electron transport material (i.e., TiZnO3 or TiO2) contained in the porous layer 3b.
[0211] [Flat band potential and carrier density]
[0212] The impedance of the solar cells of the examples and comparative examples was measured using an impedance measurement system (manufactured by Solartron Analytical, trade name: ModuLab XM), and the flat band potential and carrier density were calculated based on the method described in Non-Patent Document 3.
[0213] [Changes in the color of perovskite compounds]
[0214] The inventors of the present invention visually observed whether the color of the perovskite compound contained in the solar cells of the examples and comparative examples changed.
[0215] Tables 1 and 2 show the relative concentrations of the photoelectric conversion material, the electron transport material, and the ethyl cellulose (i.e., the pore-forming agent) in the solar cells of the Examples and Comparative Examples relative to the titanium zinc composite oxide (i.e., TiZnO3 or Ti 1.5 Zn 0.5 O3), porosity, color change of perovskite compounds, flat band potential and carrier density.
[0216] The electron transport materials shown in Table 1 and Table 2 are the electron transport materials contained in the electron transport layer 3 and in contact with the photoelectric conversion layer 4 .
[0217] [Table 1]
[0218]
[0219] [Table 2]
[0220]
[0221] As shown in Table 1, the solar cells of Examples 1 to 4 have a high flat band potential exceeding 0.9 volts because they include a photoelectric conversion layer 4 containing a tin-based perovskite compound and an electron transport layer 3 containing porous TiZnO3. Furthermore, it is believed that the solar cells of Examples 1 to 4 have a flat band potential of 2.61×10 15~5.20×10 16 The carrier density is high, so the solar cells of Examples 1 to 4 achieve high photoelectric conversion efficiency.
[0222] As shown by comparing Example 1 with Comparative Example 2, when the porous TiZnO3 has a relatively low porosity (e.g., about 0.48, see Example 1), the solar cell has a higher flat band potential than when the porous TiZnO3 has a relatively high porosity (e.g., about 0.66, see Comparative Example 2). The inventors of the present invention believe that this is because TiZnO3 is superior to TiO2 in terms of compatibility with the energy level at the lower end of the conduction band of the tin-based perovskite compound.
[0223] In the solar cells of Examples 1 to 3 and the solar cell of Comparative Example 1, a tin-based perovskite compound is used as a photoelectric conversion material. On the other hand, the solar cells of Examples 1 to 3 contain porous TiZnO3 in the electron transport layer 3, but the solar cell of Comparative Example 1 contains dense TiZnO3 in the electron transport layer 3. 1.5 Zn 0.5 In other words, in the solar cells of Examples 1 to 3, the electron transport material in contact with the tin-based perovskite compound is porous TiZnO3, but in the solar cell of Comparative Example 1, the electron transport material in contact with the tin-based perovskite compound is dense Ti 1.5 Zn 0.5 O3.
[0224] The solar cells of Examples 1 to 3 had high flat band potentials of 0.9 V or more. On the other hand, the solar cell of Comparative Example 1 had a low flat band potential of 0.59 V.
[0225] From these results, it is understood that the flat band potential can be effectively improved by using porous TiZnO 3 .
[0226] In the solar cell of Comparative Example 4, a lead-based perovskite compound and porous TiZnO3 are used as a photoelectric conversion material and an electron transport material, respectively. The solar cell of Comparative Example 4 has a high flat band potential and a low carrier density, but the lead-based perovskite compound changes from black to yellow in Example 4. This suggests that in the solar cell of Comparative Example 4, the lead-based perovskite compound is decomposed, and as a result, the function of the photoelectric conversion layer 4 is reduced.
[0227] Therefore, it is considered that when porous TiZnO 3 and a lead-based perovskite compound are used in combination, the lead-based perovskite compound decomposes.
[0228] As described above, electron transport materials suitable for tin-based perovskite compounds are different from electron transport materials suitable for lead-based perovskite compounds. Therefore, even if the same electron transport material is used in lead-based perovskite solar cells and tin-based perovskite solar cells, the performance of these solar cells is different from each other.
[0229] Industrial Applicability
[0230] The solar cell of the present application is useful as a solar cell installed on a roof, for example.
[0231] Explanation of symbols
[0232] 1 substrate
[0233] 2. First electrode
[0234] 3 Electron transport layer
[0235] 3a. Dense layer
[0236] 3b Porous layer
[0237] 4 Photoelectric conversion layer
[0238] 5 Hole transport layer
[0239] 6 Second electrode
[0240] 100 Solar Cells
[0241] 200 Solar Cells
Claims
1. A solar cell comprising: a first electrode; a second electrode; A photoelectric conversion layer disposed between the first electrode and the second electrode; and an electron transport layer disposed between the first electrode and the photoelectric conversion layer, in, At least one electrode selected from the first electrode and the second electrode has light transmittance, The photoelectric conversion layer contains 70% by mass or more of a perovskite compound formed of monovalent cations, Sn cations, and halogen anions. The electron transport layer contains 50% or more of porous TiZnO3 by molar ratio. The porous TiZnO 3 has a porosity of 20% to 70%.
2. The solar cell according to claim 1, wherein: The porous TiZnO3 has a porosity of 48% to 60%.
3. The solar cell according to claim 1 or 2, wherein: The monovalent cation includes at least one selected from the group consisting of a formamidinium cation and a methylammonium cation.
4. The solar cell according to claim 1 or 2, wherein: The halogen anion comprises an iodide ion. 5 . The solar cell according to claim 1 , further comprising a hole transport layer provided between the second electrode and the photoelectric conversion layer.
6. The solar cell according to claim 1 or 2, wherein: The porous TiZnO 3 is in contact with the photoelectric conversion layer.
Citation Information
Patent Citations
Mesoporous perovskite solar cell and preparation method thereof
CN105070836A